2007
DOI: 10.1177/0148607107031004263
|View full text |Cite
|
Sign up to set email alerts
|

Defects in Postabsorptive Plasma Homeostasis of Fatty Acids in Sickle Cell Disease

Abstract: Background-The chronic hemolytic anemia experienced by sickle cell disease (SCD) patients leads to adverse effects on oxygen transport by the blood and to a decrease in oxygen availability for peripheral tissues. Limited tissue oxygen availability has the potential to modify events of intracellular metabolism and, thus, alter lipid homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 22 publications
5
23
0
Order By: Relevance
“…We observed no significant difference in non-HDL-C levels among our participants. This to our knowledge is the first report on non-HDL-C levels in SCD and thus gives credence to the established evidence that cardiovascular disease in sickle cell disease is mostly due to pulmonary hypertension and not atherosclerosis associated with elevated levels of TC, HDL, and LDL [9, 18, 19]. …”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…We observed no significant difference in non-HDL-C levels among our participants. This to our knowledge is the first report on non-HDL-C levels in SCD and thus gives credence to the established evidence that cardiovascular disease in sickle cell disease is mostly due to pulmonary hypertension and not atherosclerosis associated with elevated levels of TC, HDL, and LDL [9, 18, 19]. …”
Section: Discussionsupporting
confidence: 69%
“…These two morbid processes disturb lipid homeostasis which in turn may lead to atherosclerosis in these patients [7, 8]. Abnormal lipid homeostasis, as well as other haematological disorders, has been reported in SCA and this has been suggested to have the potential to alter membrane fluidity and functions of red blood cells (RBC) in individuals with SCD [911]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a general alteration in the lipid balance of SCA patients but the underlying mechanisms have been poorly understood [8]. Lower plasma cholesterol levels in SCA patients compared to healthy controls were reported by many studies [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Our observation of significantly elevated fasting serum TAG concentration is in accordance with a study that reported 22% higher plasma TAG in Nigerian children with homozygous SCD compared with controls (Erasmus, Olukoga, & Ojuawo, ). Studies have also shown that patients with SCD, without documented vaso‐occlusive crises for at least 3 months, had elevated fasting plasma concentrations of TAG when compared with control participants matched for age, weight, and body fat (Buchowski et al, ; Zorca et al, ). The documented increase in fasting plasma TAG concentrations in SCD patients needs further investigation.…”
Section: Discussionmentioning
confidence: 99%